2018
DOI: 10.1021/acs.langmuir.7b04331
|View full text |Cite
|
Sign up to set email alerts
|

Floating and Tether-Coupled Adhesion of Bacteria to Hydrophobic and Hydrophilic Surfaces

Abstract: Models for bacterial adhesion to substratum surfaces all include uncertainty with respect to the (ir)reversibility of adhesion. In a model, based on vibrations exhibited by adhering bacteria parallel to a surface, adhesion was described as a result of reversible binding of multiple bacterial tethers that detach from and successively reattach to a surface, eventually making bacterial adhesion irreversible. Here, we use total internal reflection microscopy to determine whether adhering bacteria also exhibit vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…Bacterial cells are not able to overcome the energy barrier solely by their motility or Brownian motion, yet their appendages have been hypothesized to penetrate the energy barrier due to their small radii, and then effectively bridge the cell and substratum (Hori and Matsumoto, 2010). This phenomenon has been confirmed experimentally using total internal reflection microscopy (Van Der Westen et al, 2018).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 69%
See 1 more Smart Citation
“…Bacterial cells are not able to overcome the energy barrier solely by their motility or Brownian motion, yet their appendages have been hypothesized to penetrate the energy barrier due to their small radii, and then effectively bridge the cell and substratum (Hori and Matsumoto, 2010). This phenomenon has been confirmed experimentally using total internal reflection microscopy (Van Der Westen et al, 2018).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 69%
“…Energy barriers have been found to impede bacterial attachment of a wide variety of bacteria by “blocking” the cells from approaching the surfaces (Morisaki et al, 1999; Li and Logan, 2004; Feng et al, 2015). The secondary minimum, on the other hand, reflects a restriction of the bacterial movement by “trapping” the cells in an energy well (Van Der Westen et al, 2018). Bacterial cells are not able to overcome the energy barrier solely by their motility or Brownian motion, yet their appendages have been hypothesized to penetrate the energy barrier due to their small radii, and then effectively bridge the cell and substratum (Hori and Matsumoto, 2010).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 99%
“…In the original theory, bacteria were treated as colloidal round spheres, ignoring surface roughness of bacteria and surface appendages attached to the bacterial membrane (e.g., pili, fimbriae, flagella). It was suggested that surface appendages have a high probability to pierce through the energy barrier and thereby tether a bacterium to the surface [ 43 , 45 ]. At this stage, a firm anchorage between the bacterium and the surface can be established involving covalent, ionic, or hydrogen bonding [ 44 ] (Fig.…”
Section: Physicochemical Basics Of Adhesion and Adsorptionmentioning
confidence: 99%
“…Using optical microscopy, quartz crystal microbalance, or surface plasmon resonance, the number of attached cells in a certain area can be recorded over time (Filion-Côté et al, 2017;Keskin et al, 2018;Alexander et al, 2019). With the help of high-resolution optical techniques, not only the number of cells but also their motion at or above the surface can be quantified (van der Westen et al, 2018;Vissers et al, 2018). These methods can collect data of large numbers of cells simultaneously under controlled (with or without shear flow) conditions tangential to the surface.…”
Section: Experimental Setupsmentioning
confidence: 99%